2013
DOI: 10.1103/physrevb.88.174421
|View full text |Cite
|
Sign up to set email alerts
|

Spin correlations and Dzyaloshinskii-Moriya interaction in Cs2CuCl4

Abstract: We report on electron spin resonance (ESR) studies of the spin relaxation in Cs2CuCl4. The main source of the ESR linewidth at temperatures T ≤ 150 K is attributed to the uniform DzyaloshinskiiMoriya interaction. The vector components of the Dzyaloshinskii-Moriya interaction are determined from the angular dependence of the ESR spectra using a high-temperature approximation. Both the angular and temperature dependence of the ESR linewidth have been analyzed using a selfconsistent quantum-mechanical approach. I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…Electron spin resonance (ESR) was recently predicted [33] and experimentally demonstrated [34,35] to be a sensitive probe for DM interactions in spin chain systems. In the presence of DM interactions the excitation spectrum of the spin chain is shifted along the spinon propagation direction and develops a corresponding gap at zero momentum transfer.…”
Section: E Esr Spectroscopymentioning
confidence: 99%
“…Electron spin resonance (ESR) was recently predicted [33] and experimentally demonstrated [34,35] to be a sensitive probe for DM interactions in spin chain systems. In the presence of DM interactions the excitation spectrum of the spin chain is shifted along the spinon propagation direction and develops a corresponding gap at zero momentum transfer.…”
Section: E Esr Spectroscopymentioning
confidence: 99%
“…So far, experiments on CCC gave estimates for three DM parameters: D a 0 =J ∼ 5% [8] and D a;c =J ∼ 10% [25,28]. The reduced translational symmetry of the copper layers in CCC (CCB) revealed by the staggered DM vectors (3) leads to the folding of the Brillouin zone of a simple triangular Bravais lattice.…”
mentioning
confidence: 99%
“…and c, respectively. It is important to mention, that contrary to many other spin-1/2 exchange-coupled spin systems with spin interactions of the same order of magnitude [20][21][22][23], the high-temperature EPR line in Cs 2 CuBr 4 is up to two orders of magnitude broader (for comparison, the EPR linewidth in the isostructural compound Cs 2 CuCl 4 measured at T = 100 K is ~0.02-0.03 T [17], which is about 50 times smaller than the EPR linewidth in Cs 2 CuBr 4 ). Let us discuss possible contributions, which affect the EPR linewidth.…”
mentioning
confidence: 93%
“…Electron paramagnetic resonance (EPR, also known as electron spin resonance, ESR) spectroscopy is recognized as a very powerful tool to probe the anisotropy of magnetic interactions in strongly correlated spin systems. Recently performed EPR studies of Cs 2 CuCl 4 [17] provided the important information on the magnetic anisotropy in this material. It was shown that the main source of the hightemperature EPR line broadening is the Dzyaloshinskii-Moriya (DM) interaction.…”
mentioning
confidence: 99%